67th International Open Readings Conference for students of Physics and Natural Sciences. Annual Abstract Book 2024 - Keršys, Martynas; Naina, Rimantas; Adomaitis, Vincentas; Maskvytis, Emilijus (Vilnius University Proceedings, 2024)
“Open Readings 2024” is an international academic platform for students and young researchers worldwide to present their ongoing research results and practices in physics and natural sciences. The 67th International Scientific Conference for Students of Physics and Natural Sciences brings together participants to discuss, learn, exchange, and share their scientific experiences, meet key experts, and enjoy an exciting program. The conference features lectures by well-known, leading, and accomplished scientists, as well as presentations of students’ research. “Open Readings 2024” offers BSc, MSc, and PhD students an opportunity to present their scientific research to a larger audience and receive constructive criticism and helpful advice. This book provides an overview of all the presentations at the Open Readings 2024 conference.